Sulfur-containing organic ligand modified Pt nanoparticle-loaded catalyst, and preparation method and application thereof
By modifying the sulfur-containing organic ligand on the surface of the supported Pt nanoparticle catalyst, and regulating the coordination environment and electronic structure of the catalyst, the problem of selective control difficulties in the coenzyme NAD(P)+ regeneration reaction is solved, and a catalytic effect with high selectivity, high activity and high stability is achieved.
Patent Information
- Application Number
- CN202510139625.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2045-02-08
AI Technical Summary
The prior art has difficulty selectively controlling the coenzyme NAD(P)+ regeneration reaction, resulting in by-product generation, affecting catalytic efficiency and cyclic efficiency.
By modifying the sulfur-containing organic ligand on the surface of the supported Pt nanoparticle catalyst, the coordination environment and electronic structure of the catalyst are regulated, and the selectivity of the NAD(P)+ hydrogenation reaction is improved.
The catalytic effect of high selectivity, high activity and high stability was achieved, with the selectivity of NAD(P)H reaching 95%, and the conversion rate of NAD(P)+ is 100%.
Smart Images

Figure CN119588429A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a sulfur-containing organic ligand-modified loaded Pt nanoparticle catalyst, a preparation method and application thereof. Background Art
[0002] Biocatalytic reduction is an important way to prepare high value-added chemicals and pharmaceuticals. In enzymatic reactions, coenzymes act as hydrogen transfer reagents and bind to oxidoreductases, directly participating in the reaction and playing an important role. Reduced coenzyme nicotinamide adenine dinucleotide (NADH) or its phosphate form (NADPH) is a coenzyme in enzyme-catalyzed reduction. 90% of oxidoreductases require NAD(P)H (80% rely on NADH, 10% require NADPH). Since NAD(P)H is very expensive and unstable, it is not feasible to use an equimolar amount of reduced coenzymes in the enzymatic reduction process, both from an economic point of view and in practical operation. Therefore, the regeneration and recycling of coenzymes is a prerequisite for the large-scale application of enzyme reduction processes in industry.
[0003] Oxidized coenzyme NAD(P) + In addition to the production of 1,4-NADH with enzymatic activity, reduction may also produce byproducts such as 1,6-NADH and dimers that have no enzymatic activity. Once these byproducts are produced, they will greatly reduce the recycling efficiency of the coenzyme. + In the regeneration reaction, selectivity control is very challenging. In the research on coenzyme catalytic regeneration, the newly developed multiphase coenzyme hydrogenation regeneration reaction in recent years has + It is the only by-product and the heterogeneous catalyst can be recycled, so it is a green route. However, supported metal catalysts have abundant surface active sites, such as edges, corners, platforms, metal-support interfaces, etc. These different sites will show different structural sensitivities to different reactive groups. Since the active sites of supported metal catalysts are not uniform and the adsorption patterns of substrates are diverse, selectivity control is difficult. In order to improve the selectivity of heterogeneous coenzyme hydrogenation regeneration, researchers have made a lot of efforts and attempts. For example, it has been reported that the metal-support interaction can increase the NADH selectivity to 63% (ACS Sustainable Chemistry & Engineering, 2021, Vol. 9, pp. 6499-6506); the authors used a bimetallic Pt and Sn nanocatalytic strategy to regulate the NADH selectivity to 90% (Green Chemistry, 2022, Vol. 24, pp. 1451-1455).
[0004] Although the above strategies can improve the selectivity of coenzyme hydrogenation regeneration, the development of efficient, highly selective and highly stable metal catalysts remains a technical challenge in this field. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a sulfur-containing organic ligand modified supported Pt nanoparticle catalyst, preparation method and application. Similar to the ligand in homogeneous catalysis, the organic group modifies the nanoparticles, and the ligand modifies the metal active center, which can regulate the coordination environment of the active center and regulate the supported metal catalyst NAD from the two aspects of electronic effect and steric hindrance effect. + The selectivity of hydrogenation, this scheme can be used to improve the selectivity of coenzyme hydrogenation regeneration.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is a NAD(P) + A selective hydrogenation catalyst, wherein the catalyst carrier is porous silicon oxide, the catalyst contains Pt nanoparticles, the Pt content of the catalyst is 0.5-10wt%, the catalyst is modified with a sulfur-containing organic ligand, and the organic ligand content is 0.1-10 wt%. The catalyst has the characteristics of high catalytic activity, high selectivity for target products, and high stability.
[0007] In one embodiment of the present invention, the sulfur-containing organic ligand is an aliphatic thiol, an aliphatic sulfide, an aromatic thiol or an aromatic sulfide.
[0008] In one embodiment of the present invention, the structural formula of the sulfur-containing organic ligand is:
[0009] ;
[0010] Wherein, R1 and R2 are respectively selected from any one of F, Cl, Br, OCH3, CH3, OH, CN, NO2, C(CH3)3, CH(CH3)2, NH2, and SH.
[0011] In one embodiment of the present invention, the sulfur-containing organic ligand is modified on the surface of the Pt nanoparticles.
[0012] A NAD(P) + The preparation method of the selective hydrogenation catalyst comprises: impregnating porous silicon oxide into a Pt salt precursor solution by a solution impregnation method, and obtaining loaded Pt nanoparticles by drying, calcining, and high-temperature hydrogen reduction;
[0013] The organic ligand is dissolved in an organic solvent, the prepared loaded Pt nanoparticles are added into the organic ligand solution, and the loaded Pt nanoparticles modified with the sulfur-containing organic ligand are obtained by centrifugation, washing and vacuum drying.
[0014] In one embodiment of the present invention, the preparation steps are:
[0015] 1) Dissolve a soluble salt of Pt, such as chloroplatinic acid, sodium chloroplatinate or potassium chloroplatinate, in water to make a solution, immerse the carrier in the solution, and then dry it by rotary evaporation, roast it, and reduce it. The drying temperature is 20-200°C, the roasting temperature is 100-600°C, and the reduction temperature is 100-300°C.
[0016] 2) Dissolve the sulfur-containing organic ligand in an organic solvent, and treat it by ultrasound and stirring. The organic solvent is ethanol, methanol, tetrahydrofuran, ethyl acetate, chloroform, toluene, etc. The sulfur-containing organic ligand is aliphatic thiol, aliphatic sulfide, aromatic thiol and aromatic sulfide.
[0017] 3) The solid prepared in step 1 is added to the solution obtained in step 2 for impregnation and adsorption, and then centrifuged, the obtained solid is fully washed with an organic solvent, and finally vacuum dried at room temperature to obtain sulfur-containing organic ligand-modified Pt nanoparticles.
[0018] In one embodiment of the present invention, the concentration of the Pt precursor solution is 1 mM - 5 mM, the amount of solvent is 0-50 ml per 0.1 g of porous silica carrier, the immersion time of silica in the Pt salt precursor solution is 1-48 h, and the immersion temperature is room temperature to 50 °C.
[0019] In one embodiment of the present invention, the Pt salt precursor is one or a mixture of two or more of chloroplatinic acid, sodium chloroplatinate, and potassium chloroplatinate.
[0020] In one embodiment of the present invention, the solvent used in the Pt salt precursor solution is one or a mixture of two or more of water, methanol, ethanol, n-hexane, dichloromethane, and tetrahydrofuran.
[0021] In one embodiment of the present invention, the organic ligand is dissolved in an organic solvent, and the organic solvent is one or a mixture of two or more of ethanol, methanol, tetrahydrofuran, ethyl acetate, chloroform, and toluene.
[0022] In one embodiment of the present invention, the calcination temperature is 100-600° C., the calcination time is 1-5 h, the temperature of the high-temperature hydrogen is 100-300° C., and the reduction time is 1-5 h.
[0023] The NAD(P) + Selective hydrogenation catalysts in coenzyme NAD(P) + Application in hydrogenation to produce NAD(P)H.
[0024] In one embodiment of the present invention, the coenzyme NAD(P) + The hydrogenation reaction conditions are: reaction temperature 0-45 °C, H2 pressure 0.1-3 MPa.
[0025] This technical solution has the following beneficial effects:
[0026] 1) The sulfur-containing organic ligand modified Pt nanoparticle catalyst of the present invention modifies the surface of the supported metal catalyst with sulfur-containing organic ligand to regulate NAD(P) + The adsorption mode on the catalyst surface has the advantages of high catalytic activity, high selectivity for target products and high stability.
[0027] 2) The method for preparing sulfur-containing organic ligand-modified Pt nanoparticles of the present invention has the advantages of simple preparation process, low requirements for instruments and equipment, mild reaction conditions, and can prepare metal particles with uniform size and good dispersion by a simple impregnation-H2 reduction method, with an average diameter of 1-3 nm. The sulfur-containing organic ligand can be impregnated and adsorbed onto the surface of the supported metal catalyst by stirring at room temperature, and the sulfur-containing organic ligand-modified Pt nanoparticles can be obtained by simple centrifugation, washing, and drying.
[0028] 3) Application of the sulfur-containing organic ligand-modified Pt nanoparticles of the present invention to the catalyst for coenzyme NAD(P) + In the hydrogenation reaction to produce NAD(P)H, sulfur-containing organic ligands are modified on the surface of Pt nanoparticles to change the microenvironment of the catalyst surface. In addition to changing the electronic structure of Pt metal, a ligand-modified layer is formed on the surface of the metal catalyst, forming a steric hindrance effect, which only allows NAD(P) + The hydrogenation reaction occurs on the surface of Pt nanoparticles in a specific adsorption mode, which effectively inhibits the formation of by-products.
[0029] 4) The application of the sulfur-containing organic ligand modified Pt nanoparticles of the present invention inhibits the aggregation of Pt nanoparticles due to the steric hindrance effect of the sulfur-containing organic ligand, thereby improving the stability of the catalyst. The catalyst of the present invention is used to catalyze the coenzyme NAD(P) + When NAD(P)H is produced by hydrogenation, the selectivity of NAD(P)H reaches 95%, and NAD(P) + The conversion rate is 100%. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The sulfur-containing organic ligand-modified Pt nanoparticle catalyst prepared by the present invention is used for the coenzyme NAD(P) + Schematic diagram of the application of hydrogenation to produce NAD(P)H;
[0031] Figure 2 TEM and EDX images of the catalyst prepared in Example 1, wherein Figure 2 (a) is the TEM image of Example 1; Figure 2(b), (c) and (d) are EDX images corresponding to Example 1;
[0032] Figure 3 is the NAD of the catalyst prepared in Examples 1-3 and Comparative Example 1 + Graph showing hydrogenation performance versus time;
[0033] Figure 4 is the catalytic kinetic curve of the prepared catalyst, where Figure 4 (a) is the catalytic kinetic curve of Example 1, Figure 4 (b) is the catalytic kinetic curve of Comparative Example 1;
[0034] Figure 5 The cyclic stability test of the prepared catalyst is Figure 5 (a) is the cycle stability test of Example 1, Figure 5 (b) is the cycle stability test of Comparative Example 1;
[0035] Figure 6 The CO in-situ adsorption infrared spectra of the catalysts prepared in Examples 1-3 and Comparative Example 1;
[0036] Figure 7 The XPS graph of the catalyst prepared in Example 1-3. DETAILED DESCRIPTION
[0037] The schematic diagram of the application of the sulfur-containing organic ligand modified Pt nanoparticle catalyst prepared by the present invention in the reaction of hydrogenation of coenzyme NAD(P)+ to produce NAD(P)H is shown in FIG. Figure 1 As shown, the following is combined with the embodiments and the attached Figure 2 To Attachment Figure 7 The present invention is further described.
[0038] Example 1
[0039] 300 mg of porous silica was dispersed in 4 mL of chloroplatinic acid aqueous solution (containing 3 mg of Pt), stirred overnight and then evaporated to remove moisture. The sample was dried in an oven at 100 °C for 12 h, then calcined in a muffle furnace at 300 °C for 5 h, and finally reduced with H2 at 200 °C for 5 h to obtain a Pt / SiO2 catalyst with a Pt loading of 1%. 0.16 g of toluene-3,4-dithiol was dissolved in 5.0 mL of ethanol, 20 mg of Pt / SiO2 catalyst with a Pt loading of 1% was added, and the mixture was stirred at room temperature for 20 h. The mixture was thoroughly washed with ethanol, centrifuged, and finally the solid was vacuum-evacuated to remove the solvent at room temperature to obtain a toluene-3,4-dithiol-modified Pt / SiO2 catalyst. TEM results show that the Pt nanoparticles are approximately 1.7 nm ( Figure 2 (a) in the figure); EDX results show that Pt nanoparticles are uniformly dispersed on the carrier SiO2 ( Figure 2 (b), (c) and (d) in the figure.
[0040] Example 2
[0041] 300 mg of porous silica was dispersed in 4 mL of chloroplatinic acid aqueous solution (containing 30 mg of Pt), stirred overnight, and then the water was removed by rotary evaporation. The sample was dried in an oven at 100 °C for 12 h, then calcined in a muffle furnace at 400 °C for 4 h, and finally reduced with H2 at 200 °C for 4 h to obtain a Pt / SiO2 catalyst with a Pt loading of 10%. 1.7 g of adamantane thiol was dissolved in 10.0 mL of ethanol, 20 mg of a Pt / SiO2 catalyst with a Pt loading of 10% was added, and the mixture was stirred at room temperature for 20 h. The mixture was fully washed with ethanol, centrifuged, and finally the solid was vacuum-evacuated to remove the solvent at room temperature to obtain a Pt / SiO2 catalyst modified with adamantane thiol.
[0042] Example 3
[0043] 300 mg of porous silica was dispersed in 4 mL of chloroplatinic acid aqueous solution (containing 15 mg of Pt), stirred overnight, and then the water was removed by rotary evaporation. The sample was dried in an oven at 100 °C for 12 h, then calcined in a muffle furnace at 500 °C for 3 h, and finally reduced with H2 at 300 °C for 3 h to obtain a Pt / SiO2 catalyst with a Pt loading of 5%. 0.41 g of naphthalenethiol was dissolved in 10.0 mL of ethanol, 20 mg of Pt / SiO2 catalyst with a Pt loading of 5% was added, and the mixture was stirred at room temperature for 20 h. The mixture was fully washed with ethanol, centrifuged, and finally the solid was vacuum-evacuated to remove the solvent at room temperature to obtain a naphthalenethiol-modified Pt / SiO2 catalyst.
[0044] Example 4
[0045] 300 mg of porous silica was dispersed in 4 mL of chloroplatinic acid aqueous solution (containing 1.5 mg of Pt), stirred overnight and then evaporated to remove moisture, the sample was dried in an oven at 100 °C for 12 h, then calcined in a muffle furnace at 600 °C for 2 h, and finally reduced with H2 at 300 °C for 2 h to obtain a Pt / SiO2 catalyst with a Pt loading of 0.5%. 0.74 g of dibutyl sulfide was dissolved in 10.0 mL of ethanol, 20 mg of a Pt / SiO2 catalyst with a Pt loading of 0.5% was added, and the mixture was stirred at room temperature for 20 h. The mixture was fully washed with ethanol, centrifuged, and finally the solid was vacuum-evacuated to remove the solvent at room temperature to obtain a Pt / SiO2 catalyst modified with naphthylthiol.
[0046] Comparative Example 1
[0047] 300 mg of porous silica was dispersed in 4 mL of chloroplatinic acid aqueous solution (containing 3 mg of Pt), stirred overnight and then evaporated to remove moisture. The sample was dried in an oven at 100 °C for 12 h, then calcined in a muffle furnace at 300 °C for 4 h, and finally reduced with H2 at 200 °C for 2 h to obtain a Pt / SiO2 catalyst with a Pt loading of 1%.
[0048] Example 5
[0049] The application of Pt nanoparticles described in Examples 1-4 and Comparative Example 1 was to mix the catalyst (3 mg) and 2 mL NAD + The buffer (1.5 mM, pH = 8.7) was placed in an ampoule, and the reaction was started after replacing the air in the system with H2 six times. The reaction was carried out at 37°C and 2 MPa H2. After stopping the reaction, the heterogeneous catalyst and the reaction solution were separated by centrifugation, and the reaction solution was diluted to 0.075 mM with phosphate buffer. The UV-vis spectroscopy was used for quantitative detection, and the NAD + Catalytic performance of preparing NADH by hydrogenation. The NADH yields of the catalysts obtained in Examples 1-3 and Comparative Example 1 as a function of reaction time are as follows: Figure 3 As shown; the NAD+ conversion rate and NADH product selectivity of the catalysts obtained in Example 1 and Comparative Example 1 over time are respectively as shown Figure 4 (a) and Figure 4 The TOF and NADH product selectivity of the catalysts obtained in Examples 1-4 and Comparative Example 1, and the final results are shown in Table 1.
[0050] Table 1
[0051]
[0052] a NAD + When the conversion rate is 100%, the NADH product selectivity.
[0053] Example 6
[0054] The results of the stability study of the heterogeneous catalyst described in Example 1 are as follows: Figure 5 As shown in (a), it is recycled 5 times, NAD + The conversion rate was maintained at around 45%, and the selectivity of NADH was always greater than 95%, indicating that the catalyst had good stability. The stability test results of the heterogeneous catalyst described in this comparative example 1 are as follows: Figure 5 As shown in (b), as the number of cycles increases, NAD + The conversion rate decays exponentially. After the catalyst described in Comparative Example 1 is surface modified with an organic ligand, the stability of the heterogeneous catalyst is greatly improved.
[0055] Example 7
[0056] Comparative Example 1: Since there is no organic ligand modification layer on the catalyst surface, the active sites on the surface of Pt nanoparticles are not uniform. + There are many adsorption modes on the catalyst surface, which leads to a decrease in the selectivity of NADH products. In addition to the enzymatically active 1,4-NADH, the inactive 1,6-NADH is also generated.
[0057] Example 8
[0058] The catalysts prepared in Examples 1-3 and Comparative Example 1 were subjected to in-situ infrared spectroscopy test for CO adsorption ( Figure 6 ) and XPS characterization analysis ( Figure 7 ). It was found that after modification with sulfur-containing organic ligands, the linear CO adsorption peak was greatly weakened, and the maximum absorption peak moved to a lower wave number. The presence of S had a certain electron-donating effect on the active center Pt, resulting in an increase in the charge density of Pt. XPS characterization results showed that Pt δ+ The ratio increases, metallic Pt 0 The shift to lower binding energy means that the Pt surface is more electron-rich. The in-situ infrared spectrum of CO adsorption is consistent with the XPS characterization results.
[0059] The above specific embodiments are only used to illustrate the present invention rather than to limit the present invention. Any changes and substitutions made to the present invention without creative work within the scope of protection of the present invention and the claims shall fall within the scope of protection of the patent of the present invention.
Claims
1. A NAD(P) + A selective hydrogenation catalyst, characterized in that The carrier of the catalyst is porous silicon oxide, the catalyst contains Pt nanoparticles, the Pt content of the catalyst is 0.5-10 wt%, and the catalyst is modified by sulfur-containing organic ligands, and the content of the organic ligands is 0.1-10 wt%.
2. NAD(P) according to claim 1 + A selective hydrogenation catalyst, characterized in that The sulfur-containing organic ligand is aliphatic thiol, aliphatic thioether, aromatic thiol or aromatic thioether.
3. NAD(P) according to claim 2 + A selective hydrogenation catalyst, characterized in that The structural formula of the sulfur-containing organic ligand is: ; Wherein, R1 and R2 are respectively selected from any one of F, Cl, Br, OCH3, CH3, OH, CN, NO2, C(CH3)3, CH(CH3)2, NH2, and SH.
4. NAD(P) according to any one of claims 1 to 3 + A selective hydrogenation catalyst, characterized in that Sulfur-containing organic ligands are modified on the surface of Pt nanoparticles.
5. A NAD(P) + A method for preparing a selective hydrogenation catalyst, characterized in that: The porous silicon oxide is impregnated into a Pt salt precursor solution by a solution impregnation method, and the loaded Pt nanoparticles are obtained by drying, calcining, and high-temperature hydrogen reduction; The organic ligand is dissolved in an organic solvent, the prepared loaded Pt nanoparticles are added into the organic ligand solution, and the loaded Pt nanoparticles modified with the sulfur-containing organic ligand are obtained by centrifugation, washing and vacuum drying.
6. The preparation method according to claim 5, characterized in that: The concentration of the Pt precursor solution is 1 mM - 5 mM, the amount of solvent is 0-50 ml of solvent per 0.1 g of porous silicon oxide carrier, the immersion time of silicon oxide in the Pt salt precursor solution is 1-48 h, and the immersion temperature is room temperature to 50°C.
7. The preparation method according to claim 5, characterized in that: The Pt salt precursor is one of chloroplatinic acid, sodium chloroplatinate, potassium chloroplatinate, or a mixture of two or more thereof.
8. The preparation method according to claim 5, characterized in that: The solvent used in the Pt salt precursor solution is one or a mixture of two or more of water, methanol, ethanol, n-hexane, dichloromethane, and tetrahydrofuran.
9. The preparation method according to claim 5, characterized in that: The calcination temperature is 100-600°C, the calcination time is 1-5 h, the temperature of the high-temperature hydrogen is 100-300°C, and the reduction time is 1-5 h.
10. NAD(P) according to any one of claims 1 to 4 + Selective hydrogenation catalysts in coenzyme NAD(P) + Application in hydrogenation to produce NAD(P)H.
Citation Information
Patent Citations
Polydentate heteroatom ligand containing metal complexes, catalysts and methods of making and using the same
CN101356006A
Uses of certain platinoid accumulating plants for use in organic chemical reactions
CN105579130A
ZSM-12 molecular sieve supported high-dispersion Pt catalyst and preparation method thereof
CN109772443A
Tridentate ligand modified silica gel immobilized platinum-containing hydrosilylation catalyst and preparation method thereof
CN112169840A
Preparation of supported platinum nano-cluster catalyst and application of supported platinum nano-cluster catalyst in alkane anaerobic dehydrogenation
CN114011472A